PENGARUH LKPD BERBASIS MODEL DISCOVERY LEARNING PADA MATERI ROTASI BENDA TEGAR DAN FLUIDA TERHADAP PENCAPAIAN KOMPETENSI FISIKA PESERTA DIDIK KELAS XI SMAN 15 PADANG - Selvi Febriani Erdi; Yulkifli Yulkifli; Murtiani Murtiani (PILLAR OF PHYSICS EDUCATION, 2017)
Achievement of the competence of learners on the subjects of physics showed less than optimal results because the learning model and teaching materials have not demanded the active role of learners in finding the concept. Physics learning requires instructional materials based on learning models that can increase the interaction of learners in a concept invention. The teaching materials in question are Student Work Sheets based on the Discovery Learning model. The purpose of this research is to investigate the influence of Student Work Sheets based on Discovery Learning model on the material of rotation of rigid bodies and fluids objects to the achievement of physics competence of students of class XI SMAN 15 Padang. This type of research is Quasi Experiment Research with Randomized Control Group Design Only Design. The population of the study were students of class XI SMAN 15 Padang registered in the academic year 2016/2017 with the sampling technique used was cluster random sampling. The experimental class is XI IPA 1 using Student Work Sheets based on Discovery Learning model and control class is XI IPA 5 using Student Work Sheets in the school. Assessment instruments used in attitudinal aspects through the assessment of observation, knowledge through written tests, and skills through performance appraisal. Research data were analyzed by two equality test equation using t test statistic and regression test and correlation to know the relation between independent variable and control variable. The mean value of the experimental class attitude aspect is 82,11 and the control class is 72,45. The average value of the experimental class knowledge aspect is 80,12 and the control class is 72,34. The average value of experimental class skill aspect is 79,21 and the control class is 66,33. The result of t test for attitude aspect is 3,1569, knowledge is 2,5605, and skill is 6,4236 show t count is outside acceptance area of Ho. It shows that the difference of mean value between the two sample classes has significance at the real level of 0,0500 with the value of t count > t table. Based on the regression and correlation test, the effect of Student Work Sheets based on the Discovery Learning model on the knowledge aspect is 21,19 %. So, it can be concluded that there is a significant effect on the use of Student Work Sheets based on the model of Discovery Learning toward the achievement of physics competence of students of class XI SMAN 15 Padang